Experience of Integrating Humanities and Natural Sciences into the Educational Environment; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Kukhta M. S. Maria Sergeevna; Homushku O. Olga; Kornienko M. Mikhail; Kutsenko L. Larisa (2015, 2015)
Title screen